Fiscal policy and natural resource entitlements: Who benefits from Mexican oil? - Paul Segal (The Oxford Institute for Energy Studies, 2012)
This paper suggests a new approach to analysing the distribution of natural resource revenues and applies it to the case of Mexico. It defines a natural resource entitlement as a citizen's per capita share of their country's natural resource rents. The main finding is that, according to official estimates, Mexican fiscal policy transfers oil entitlements from the bottom 90 percent of the population to the top 10 percent of the population. This implies that, although fiscal policy is progressive relative to market income, it is regressive once oil entitlements are taken into account. I consider a fiscal reform that would ensure that every citizen received their oil entitlement, and in doing so would eliminate extreme poverty.
Keywords: 330; Erdölvorkommen; Finanzpolitik; Verteilungswirkung; Mexiko